Recent advances in pathogenesis, assessment, and treatment of atherosclerosis [version 1; referees: 3 approved] - J. David Spence (F1000Research, 2016)
In recent years, there have been a number of advances in the pathogenesis and treatment of atherosclerosis and in assessing prognosis in carotid atherosclerosis. Risk stratification to improve vascular prevention by identifying patients most likely to benefit from intensive therapy is much improved by measuring carotid plaque burden. In patients with asymptomatic carotid stenosis, a number of modalities can be used to identify the 10-15% who could benefit from endarterectomy or stenting. Transcranial Doppler embolus detection, echolucency and ulceration on 3D ultrasound, intraplaque hemorrhage on magnetic resonance imaging (MRI), and reduced cerebrovascular reserve are useful already; new approaches including plaque texture on ultrasound and imaging of plaque inflammation and early calcification on positron emission tomography/computed tomography (PET/CT) are in development. The discovery that the intestinal microbiome produces vasculotoxic metabolites from dietary constituents such as carnitine in meat (particularly red meat) and phosphatidylcholine from egg yolk and other sources has revolutionized nutritional aspects of vascular prevention. Because many of these vasculotoxic metabolites are removed by the kidney, it is particularly important in patients with renal failure to limit their intake of red meat and egg yolk. A new approach to lowering low-density lipoprotein (LDL) cholesterol by blocking the action of an enzyme that destroys LDL receptors promises to revolutionize vascular prevention once less costly treatments are developed, and a new approach to vascular prevention—“treating arteries instead of risk factors”—shows promise but requires randomized trials. These advances all promise to help in the quest to prevent strokes in high-risk patients.